Visible-Light-Promoted C2 Trifluoromethylation of Quinoline N-Oxides - Liang, Ce; Zhuo, Wang-Tao; Niu, Yan-Ning; Gao, Guo-Lin (Synthesis, 2020)
A photoredox catalytic strategy has been described for the direct C2 trifluoromethylation of quinoline N-oxides. This reaction is compatible with a range of synthetically relevant functional groups for providing efficient synthesis of a variety of C2 trifluoromethyl quinoline N-oxides at room temperature. Mechanistic studies indicated that the reaction proceeds via a radical pathway.
Keywords: trifluoromethylation; photoredox; C–H functionlization; radicals; N-oxide compounds